2020
DOI: 10.5664/jcsm.8628
|View full text |Cite
|
Sign up to set email alerts
|

The effect of playing a wind instrument or singing on risk of sleep apnea: a systematic review and meta-analysis

Abstract: Study Objectives: To systematically survey the scientific literature concerning the effect of playing a wind instrument or singing on sleep, snoring, and/or obstructive sleep apnea. Methods: The PubMed, EMBASE, and Cochrane databases were searched up to December 2019. Observational studies and (Randomized) Controlled Clinical Trials that assessed sleep, snoring, or obstructive sleep apnea as clinical outcome or via a questionnaire were included. For the individual studies, the potential risk of bias was scored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Overall, van der Weijden et al's study 12 supports favorable effects of playing certain wind instruments and singing in alleviating symptoms and risk of snoring and OSA. However, future research in the role of myofunctional therapy as a therapeutic adjunct will require large, population-based, randomized controlled studies with standardized exercises that are observed over a sufficient lead time to measure any positive effects on symptoms and severity of snoring and OSA.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Overall, van der Weijden et al's study 12 supports favorable effects of playing certain wind instruments and singing in alleviating symptoms and risk of snoring and OSA. However, future research in the role of myofunctional therapy as a therapeutic adjunct will require large, population-based, randomized controlled studies with standardized exercises that are observed over a sufficient lead time to measure any positive effects on symptoms and severity of snoring and OSA.…”
mentioning
confidence: 84%
“…In this issue of Journal of Clinical Sleep Medicine, the paper by van der Weijden et al 12 reports a systematic review and metaanalysis of present scientific literature illustrating the role of playing musical wind instruments or singing in alleviating the risk of OSA, snoring, and related symptoms of sleep disturbance and daytime sleepiness. The authors included observational and/or randomized controlled studies where active participants either played a wind instrument or sang, and outcomes evaluating sleep such as snoring, risk of OSA, physician diagnosis of OSA, apnea-hypopnea index, and daytime sleepiness were compared with the control group (nonplayers, nonsingers, or healthy volunteers).…”
mentioning
confidence: 99%
“…Myofunctional therapy consists of interventions such as electrical stimulation of the tongue, 60,61 speech therapy, 62,63 circular breathing, singing, or wind-instrument playing, 64,65 which strengthen the facial, tongue, oropharyngeal, or skeletal structures and enhance the neuromuscular compensatory mechanisms that counteract the anatomic mechanical loads contributing to airway narrowing. 66,67 A European task force did not recommend myofunctional therapy as a standard treatment of obstructive sleep apnea, based on limited and low-quality evidence.…”
Section: Myofunctional Therapymentioning
confidence: 99%
“…Future study using simple ECG derived EMG signals may help inform the unique components of volitional apnea that might be beneficial to harness as a therapeutic or training tool in OSA and epilepsy. Importantly, breath training of other types, such as singing (Courtney, 2020;van der Weijden et al, 2020) and restrictive breathing (Kido et al, 2013) has been proposed to help patients with OSA.…”
Section: Broader Utility Of a Voluntary Obstructive Apnea Modelmentioning
confidence: 99%